FUNCTIONAL TRAINING BASE SYNTAX OF SIMPLE SENTENCES OF FUTURE TEACHERS OF UKRAINIAN LANGUAGE AND LITERATURE: LINGUISTIC COMMENT - Druzhenenko, Rayisa S. (Educological discourse, 2015)
In the article  it is presented studying the syntax of a simple sentence of the future teachers of the language and literature in functional basis, justified the semantic, cognitive, communicative, pragmatic aspects of syntactic functionalism.